The Construction of Law Neutrality of State Civil Apparatus in the Simultaneous Local Election in Indonesia - Agus Riwanto (Yuridika, 2019)
This article will examine and explore the urgency of the state's civil apparatus to be neutral in the simultaneous local election. State civil apparatus is an apparatus that works to serve the public interest rather than serve a particular group. That is why the need for the construction of constitutional law in an effort to create regulations in order the state civil apparatus has to be neutral. The construction by progressive constitutional law is by looking for new ways or role breaking and innovative breakthroughs, if the normal way and normative unable to immediately realize the objectives of the simultaneous local elections. There are three ways: First, to revoke the right to vote of state civil apparatus in the general election. Second, models political apointee  bureaucracy in the local government. Third, change the model of career guidance state civil apparatus fom government regional autonomy to the central government by rank or class.